2019
DOI: 10.1186/s42358-019-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of juvenile idiopathic arthritis in schoolchildren from the city of São Paulo, the largest city in Latin America

Abstract: Background: Juvenile idiopathic arthritis (JIA) is a chronic inflammatory disease that affects children and adolescents. Its prevalence varies greatly from one study to another according to the population and methodology. Some tools may be helpful in screening for suspected cases. The aim of this study is determine the prevalence of JIA in children and adolescent students in the city of São Paulo, Brazil. Methods: This cross-sectional study was conducted from March 2016 to November 2017. It was based on a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The global prevalence of JIA shows considerable variation and while our hospital based data likely underestimate the true population prevalence [ 24 , 25 ], the 2012 point-prevalence is at the higher end of prevalence estimates reported from other hospital-based studies [ 12 , 26 ]. However, it remains well below the estimated prevalence reported from a previous cross-sectional Australian study of 12 year-old metropolitan students where approximately 4/1000 were found to have JIA [ 25 ], while similar studies from Belgium (in children aged 12–18 years) and a recent study from Brazil (children aged 1–16 years) found community-based prevalence estimates of 1.7 and 2 per 1000 children, respectively [ 27 , 28 ]. Together these data illustrate that there is a number of patients with JIA that have milder and/or spontaneously remitting JIA, that will not be captured in hospital-based data [ 29 ].…”
Section: Discussionmentioning
confidence: 66%
“…The global prevalence of JIA shows considerable variation and while our hospital based data likely underestimate the true population prevalence [ 24 , 25 ], the 2012 point-prevalence is at the higher end of prevalence estimates reported from other hospital-based studies [ 12 , 26 ]. However, it remains well below the estimated prevalence reported from a previous cross-sectional Australian study of 12 year-old metropolitan students where approximately 4/1000 were found to have JIA [ 25 ], while similar studies from Belgium (in children aged 12–18 years) and a recent study from Brazil (children aged 1–16 years) found community-based prevalence estimates of 1.7 and 2 per 1000 children, respectively [ 27 , 28 ]. Together these data illustrate that there is a number of patients with JIA that have milder and/or spontaneously remitting JIA, that will not be captured in hospital-based data [ 29 ].…”
Section: Discussionmentioning
confidence: 66%
“…JIA is characterized by chronic synovitis and extra-articular manifestations and is diagnosed according to the criteria established by the International League of Associations for Rheumatology (ILAR) [1]. JIA prevalence in the city of Sao Paulo (Brazil) is 1.96 of 1000 schoolchildren from 1 to 16 years old [2].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of JIA differs according to the classification used and methodological issues, among other factors, ranging from 3.8 to 400 cases per 100,000 3 . In Brazil, the disease has a prevalence of 196 per 100,000 children 4 …”
Section: Introductionmentioning
confidence: 99%